2014
DOI: 10.1007/s12013-014-9918-3
|View full text |Cite
|
Sign up to set email alerts
|

Activated Human Hepatic Stellate Cells Promote Growth of Human Hepatocellular Carcinoma in a Subcutaneous Xenograft Nude Mouse Model

Abstract: Tumor cell microenvironment defines cancer development, also in hepatocellular carcinoma (HCC). Hepatic stellate cells (HSCs) are believed to be the key contributors to tumor microenvironment in HCC, yet their precise role in cancer progression is still unclear. The aim of this study was to determine the effect of human HSCs on progression of HCC using a subcutaneous xenograft nude mouse model. Nude mice were stratified to receive subcutaneous injections of human HCC cell line HepG2 and human HSC line LX-2 (He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Activated HSCs produce numerous angiogenic factors such as VEGF (90, 145) and angiopoietin 1 (Angpt1) 1 or Angpt2 (91, 146, 147), which activate their respective receptors on endothelial cells to enhance their functions (143) and promote tumor vascularization and growth. This has been shown in numerous in vitro and in vivo studies using HSC/endothelial cell coculture systems and in tumor cell/HSC coimplantation models (90, 148150). VEGF is a potent survival factor for endothelial cells that promotes their proliferation and vascular permeability thus supporting the formation of new vasculature.…”
Section: Hepatocellular Carcinomamentioning
confidence: 70%
“…Activated HSCs produce numerous angiogenic factors such as VEGF (90, 145) and angiopoietin 1 (Angpt1) 1 or Angpt2 (91, 146, 147), which activate their respective receptors on endothelial cells to enhance their functions (143) and promote tumor vascularization and growth. This has been shown in numerous in vitro and in vivo studies using HSC/endothelial cell coculture systems and in tumor cell/HSC coimplantation models (90, 148150). VEGF is a potent survival factor for endothelial cells that promotes their proliferation and vascular permeability thus supporting the formation of new vasculature.…”
Section: Hepatocellular Carcinomamentioning
confidence: 70%
“…Activated HSCs in cellular cultures. It has been shown that HSC activation plays a crucial role in supporting inflam- mation and growth of early tumor cells in HCC (26)(27)(28)(29). Morphological evaluation of cultured cells supported the presence of HSCs.…”
Section: Comparative Analysis Of Cell Growth Curves Between Cp-hep Anmentioning
confidence: 86%
“…Angiogenesis is a hypoxia-stimulated and growth-factor mediated process in which new vessels are formed from the existing vasculature [62]. This has been shown in numerous in vitro and in vivo studies using HSC/endothelial cell co-culture systems and in tumor cell/HSC co-implantation models [39,40,66,67]. This has been shown in numerous in vitro and in vivo studies using HSC/endothelial cell co-culture systems and in tumor cell/HSC co-implantation models [39,40,66,67].…”
Section: Hscs May Promote Tumor Angiogenesismentioning
confidence: 97%
“…In a subcutaneous co-transplantation model, the presence of an HSC cell line increased tumor formation by neoplastic MIMR hepatocytes two-to threefold [38]. Subcutaneous implantation of HepG2 cells and the HSC cell line LX2 in nude mice resulted in more rapid tumor growth and increased tumor size and weight relative to control animals who received HepG2 alone [39]. Subcutaneous implantation of HepG2 cells and the HSC cell line LX2 in nude mice resulted in more rapid tumor growth and increased tumor size and weight relative to control animals who received HepG2 alone [39].…”
Section: Hscs As Component Of the Tme And Contributors To Hcc Progresmentioning
confidence: 97%
See 1 more Smart Citation